Modified astrophysical S-factor of 12C+12C fusion reaction at sub-barrier energies *Supported by the National Key Research and Development Program of China (2016YFA0400501), National Natural Science Foundation of China (11805291, 11575292, 11475228, 11490564, 11875329), the U.S. Department of Energy ( DE-AC07-05ID14517), Fundamental Research Funds for the Central Universities (18lgpy84), Continuous Basic Scientific Research Project (WDJC-2019-13), CNNC R&D program (FA18000201). X. D. Tang thanks the support of the Strategic Priority Research Program of Chinese Academy of Sciences (XDB34000000) and the "Hundred Talents Program" of the Chinese Academy of Sciences. (November 2020) - Li 李, Y. J. 云居; Fang 方, X. 晓; Bucher, B.; Li 李, K. A. 阔昂; Ru 茹, L. H. 龙辉; Tang 唐, X. D. 晓东
Abstract: The 12 C+ 12 C fusion reaction plays a crucial role in stellar evolution and explosions. Its main open reaction channels include, p, n, and 8 Be. Despite more than a half century of efforts, large differences remain among the experimental data of this reaction measured using various techniques. In this work, we analyze the existing data using a statistical model. Our calculation shows the following: 1) the relative systematic uncertainties of the predicted branching ratios decrease as the predicted ratios increase; 2) the total modified astrophysical S -factors ( S * factors) of the p and channels can be obtained by summing the S * factors of their corresponding ground-state transitions and the characteristic rays, while taking into account the contributions of the missing channels to the latter. After applying corrections based on branching ratios predicted by the statistical model, an agreement is achieved among the different data sets at E cm > 4 MeV, while some discrepancies remain at lower energies, suggesting the need for better measurements in the near future. We find that the S * factor recently obtained from an indirect measurement is inconsistent with the direct measurement value at energies below 2.6 MeV. We recommend upper and lower limits for the 12 C+ 12 C S * factor based on the existing models. A new 12 C+ 12 C reaction rate is also recommended.